Inside Back Cover: Toluene Dioxygenase‐Catalysed Oxidation of Benzyl Azide to Benzonitrile: Mechanistic Insights for an Unprecedented Enzymatic Transformation (ChemBioChem 4/2016). (February 2016) - Vila, María Agustina; Pazos, Mariana; Iglesias, César; Veiga, Nicolás; Seoane, Gustavo; Carrera, Ignacio
Abstract : The inside back cover picture shows the first enzymatic conversion of an alkyl azide to a nitrile catalysed by the toluene dioxygenase enzymatic complex. A plausible mechanism for this transformation and involves an initial benzylic monooxygenation followed by a nitrene‐mediated rearrangement to form an oxime that is further dehydrated to afford the nitrile. This is the first report to describe an oxime‐dehydration activity by a Rieske dioxygenase. More information can be found in the communication by I. Carrera et al. onpage 291 in Issue 4, 2016 (DOI:10.1002/cbic.201500653 ).